STUDI TENTANG PENGGUNAAN GOOGLE SCHOLAR SEBAGAI SUMBER BELAJAR PKN (Studi Deskripsi Pendapat Mahasiswa S1 PKn Universitas Pendidikan Indonesia) - Ikbal, - (2020)
Civics education is a multidisciplinary education composed of various sciences like a politics, law, social, moral values, and the science of citizenship. The implementation of civics education learning must be supported by complete learning resources in order to meet information needs such as Google Scholar. This research aims to analyze the benefits of using Google Scholar as a source of Civics learning. This research uses a qualitative approach with descriptive methods. This research was conducted at the Department of Civics Education at the Universitas Pendidikan Indonesia with lecturers and students as interviewees. Data collection in this research was carried out through observation, interviews, and document analysis. Data analysis techniques used through triangulation techniques. Data were analyzed through data reduction, data presentation, and conclusions. The results of this research are (1) The students view on the use of Google Scholar as a source of civics learning is Goggle Scholar really provides convenience in finding knowledge that is difficult to obtain from books. (2) The reason students use Google Scholar as a civics learning source is that Google Scholar is able to facilitate users who want to read literature from various disciplines, such as articles, papers, books and scientific works. (3) The advantages of Google Scholar as a source of Civics learning is a source of scientific reference and Up-date and the lack of Google Scholar as a source of Civics learning is prone to getting caught in plagiarism, and not all students know and use it.